2020
DOI: 10.1002/lary.29140
|View full text |Cite
|
Sign up to set email alerts
|

Upper Lip Tie: Anatomy, Effect on Breastfeeding, and Correlation With Ankyloglossia

Abstract: Objectives There is debate among otolaryngologists and other practitioners about whether upper lip tie contributes to difficulty with breastfeeding and whether upper lip tie and ankyloglossia are linked. Our objectives were to evaluate the anatomy of the upper lip (maxillary) frenulum, to determine if the visual anatomy of the upper lip has an effect on breastfeeding, and to determine whether the occurrence of lip tie and tongue tie are correlated. Methods A prospective cohort study of 100 healthy newborns was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 19 publications
(28 reference statements)
1
33
0
Order By: Relevance
“…Santa Maria found that the Kotlow classification had poor interrater reliability [ 29 ]. Two studies reported no correlation between the maxillary lip score by the Kotlow classification and breastfeeding outcomes in the newborn nursery [ 30 , 31 ]. Mills’ Cine MR visualization of healthy breastfeeding infants, showed that the majority did not evert their upper lip while breastfeeding [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Santa Maria found that the Kotlow classification had poor interrater reliability [ 29 ]. Two studies reported no correlation between the maxillary lip score by the Kotlow classification and breastfeeding outcomes in the newborn nursery [ 30 , 31 ]. Mills’ Cine MR visualization of healthy breastfeeding infants, showed that the majority did not evert their upper lip while breastfeeding [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“… 31 , 32 Of note, all the infants being diagnosed and treated for both tongue and lip-tie in this study contradicts prior work where researchers did not find an association between these 2 anomalies occurring concurrently. 33 Future research should be directed at both a larger and more diverse sample, with a variety of tongue-tie classifications and functional assessments, and specific evaluation between infants with and without concomitant lip-tie. It is important to note that the Kotlow criteria has not been assessed for reliability or validity.…”
Section: Limitationsmentioning
confidence: 99%
“…The normal spectrum of labial frenula anatomy is not linked with breastfeeding problems, and should not be pathologized as restricted or ‘tied’. 129 – 131 There is no anatomic or functional basis for the diagnosis of posterior tongue-tie. 72 , 94 , 95 , 132 The latter two diagnoses are examples of overmedicalization of breastfeeding problems, resulting in exponential increase in unnecessary infant oral surgery and bodywork exercises.…”
Section: Prevention and Management Of Lactation-related Nipple Painmentioning
confidence: 99%